IKLIM KERJA POSITIF DI SEKOLAH: PERSEPSI GURU SEKOLAH MUHAMMADIYAH - Ika Fitriana; Enung Hasanah; Hendro Widodo (At Turots: Jurnal Pendidikan Islam, 2024)
This study is motivated by the need for a positive work climate in Muhammadiyah schools, which is essential to support teacher comfort, productivity, and job satisfaction. However, some schools still face challenges, such as insufficient support, ineffective communication, and gaps in individual development, impacting teacher collaboration and work quality. Therefore, this study aims to identify the characteristics of a positive work climate and its supporting factors from the perspective of teachers in Muhammadiyah schools. The research uses a qualitative approach with five participants who are teachers from Muhammadiyah Schools in Gunungkidul. Data was collected through online interviews via Google Forms and then analyzed using thematic analysis to identify relevant patterns in respondent perceptions. The findings reveal four main characteristics of a positive work climate: support, comfort, opportunities for development, and the absence of gaps among members. Additionally, factors influencing the work climate in schools include leadership, problem-solving methods, and individual attitudes. Strategies to create a positive work climate involve fostering good cooperation, open communication, mutual respect, and regard among organization members. This study provides valuable insights for school administrators in creating a supportive work environment that enhances teacher work quality and well-being, ultimately contributing positively to the achievement of educational goals in Muhammadiyah schools.